Glosa do wyroku Naczelnego Sądu Administracyjnego z dnia 7 sierpnia 2024 r., III FSK 1148/23 - Księżak, Paweł (PRAWO i WIĘŹ, 2025)
In the commented judgment, the NSA aptly assumed that the subject of inheritance and gift tax can only be the definitive acquisition of the object of the donation. It would be contrary to the purpose of the law, the constitutional principle of proportionality and justice to charge tax in the absence of a definitive acquisition by the part of the recipient, which is the case when a donation is revoked. It should be considered that other situations where there is a revocation of a donation under various civil law provisions should be assessed in the same way. However, a critical assessment is required of the SAC's recognition that a donation has been revoked in a particular case.